Enhancing community-based earthquake disaster management: resident preferences and adaptive capacity for resilience - Bih-Chuan Lin; Chun-Hung Lee (Geomatics, Natural Hazards & Risk)
Earthquake disasters remain a persistent global challenge, requiring innovative approaches to disaster management. Community-based earthquake disaster management (CBEDM) integrates social, environmental, and political factors, emphasizing residents’ adaptive capacity and disaster prevention preferences. This study employs the Choice Experiment (CE) method within an adaptive capacity framework to “quantify residents’ preferences, adaptive behaviours, and willingness to participate (WTP)” in CBEDM scenarios. Using the Random Parameter Logit (RPL) model, the research reveals strong community support for CBEDM programs and highlights three key findings: first, “collaboration between local governments, non-profits, and communities enhances disaster preparedness and post-disaster recovery”; second, “active community participation reduces disaster impact and raises awareness”; third, “empowering social organizations ensures efficient recovery services and social inclusion.” These insights provide evidence-based recommendations for aligning disaster management strategies with residents’ preferences and fostering adaptive behaviours to mitigate earthquake risks.